Status Fosfat Organik dalam Tanah Siri Bungor dengan Sistem Tanaman Tunggal dan Giliran - Hussin, Aminuddin; Saad, Abdul Kadir; Abd Rahim, Anuar; Yusop, Mohd Khanif (1984)
An experiment was carried out to ascertain the status of organic phosphorus (P) and its contribution to P source for plants under monoculture (maize) and crop rotation (groundnut and maize) systems. The amount of organic P in both cropping systems was in the range of 40-50% of total P in P fertilized soils and 70-80% of total P in non P fertilized soils. Mineralization at a rate 0.2 to 16% of the amount of organic P if/, the soil in a cropping season was detected and this can contribute to 1 to 60 kg P ha'l for the plants. The C:P ratio in both systems was in the range of 140-160:1 which encouraged mineralization.